Diversity, Equity and Inclusion (DEI): a close look into the organizational safeguarding at PRATAY - Badruddoza, Md Rakin Zarif (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, 2024.